ANALISIS BAHAN KIMIA OBAT NATRIUM DIKLOFENAK DALAM SEDIAAN JAMU ASAM URAT YANG BEREDAR DI KOTA TIMIKA - Maryam, St.; Suhaenah, Asriani; Rusniyanti, Rusniyanti (Fakultas Farmasi UMI, 2023)
Uric acid herbs are an alternative that is still widely used by the community as an anti-inflammatory and pain reliever. The increasing public interest in returning to traditional medicine has prompted several manufacturers to add medicinal chemicals to their preparations to produce a faster and maximum therapeutic effect, one of which is diclofenac sodium. The study aimed to analyze the chemical ingredients of the uric acid herbs circulating in Timika City and to find out the level of diclofenac sodium contained therein. The method used is High Performance Liquid Chromatography (HPLC) with reverse phase, where the mobile phase is methanol: aquabidestilata (80:20) and the stationary phase is column C-18. Based on the test results, nine uric acid herbs showed positive results with retention times at the same value as diclofenac sodium. The content of diclofenac sodium obtained were code A herb of 4.135 mg/L, B herb : 36.300 mg/L, C herb : 18.530 mg/L, herb D : 473.219 mg/L, herb E : 40.991 mg/L, herb F : 77.165 mg/L L, herb G : 93.109 mg/L, herb H : 52.700 mg/L, and herb I : 297.123 mg/L. All herb samples tested were unfit for public use because they contained the chemical drug sodium diclofenac